How Ibrahim came to know Allah? - Khan, Saniyasnain; Gurmeet (Goodword Books New Delhi, 2008)
"How Ibrahim Came to Know Allah" is a captivating story that recounts the journey of the Prophet Ibrahim (Abraham) in his quest for understanding and faith in Allah. The narrative illustrates Ibrahim's deep contemplation of the world around him, leading him to question the nature of divinity and the idols worshipped by his community. Through a series of revelations and profound experiences, Ibrahim discovers the oneness of Allah, embracing monotheism and becoming a pivotal figure in the spiritual heritage of Islam, Judaism, and Christianity. This story emphasizes themes of inquiry, belief, and the importance of seeking truth, inspiring readers to reflect on their own paths to understanding faith.